The effects of a training course in non-verbal communication skills of Iranian dental students - Falah-Kooshki , Sepideh; Sheibaninia, Ahmad; Jahanbani, Jahanfar (The journal of contemporary issues in business and government, 2021)
Purposes:Non- verbal communication(NVC) is crucial for dental clinicians.The goals of the present study were to evaluate the initialleve lNVC skills indental students and whether or not further,focused education in this area can improve these skills. Materials and Methods: In this clinical trial,77 dental-school students out of 104 samples who hadless than 80% of communication skills ’indicators were included and randomly allocated into experimental and control groups.The ones receiving more than 80% were excluded from the study. Students allocated to the experimental group were educated for 1hour in communication indicator s ,while the control group received no training.After 2 weeks,the communication skills of both groups were evaluated by10 indicators when working with real patients.The evaluator, proficient in NVC skills , was blinded as to the groups . There sults were analyzed by Mann-Whit ney U and Fischer exact testusing SPSS version 23.